beastboy03
beastboy03
03-05-2017
Mathematics
contestada
Simplify 2x-(3•0.6x+2.7)
Respuesta :
nbjcoolman
nbjcoolman
03-05-2017
Let's simplify step-by-step.
2x
−
(
(3)
(0.6)
x
+2.7
)
Distribute the Negative Sign:
=
2x
+
−1
(
(3)
(0.6)
x
+2.7
)
=
2x
+
−1
(3)
(0.6)
x
+
(
−1
)
(2.7)
=
2x
+
−
1.8x
+
−2.7
Combine Like Terms:
=
2x
+
−
1.8x
+
−2.7
=
(
2x
+
−
1.8x
)
+
(
−2.7
)
=
0.2x
+
−2.7
Answer:
=
0.2x
−
2.7
Good luck mate :P
Answer Link
VER TODAS LAS RESPUESTAS ( 44+ )
Otras preguntas
1.Amina bought 112 toffees each at GH40.45p. She sold each at GH40.53p. Find the total amount she bought the toffees, correct to 2 decimal places received from
Please Help ASAP! (See Attached) - Brainliest + 100 pts!!!
PLEASE HELP Will the answer be A) or D) there is confusion. I think it is D but it might be A because the figure has 1 hexagon, 2 pentagons, 2 squares and in th
What changes have occurred in Paul in the book a Lesson Before Dying
Why sugar is an organic compound
Assume m1 = 1 kg, m2 = 3 kg, and x1 = 1 m, x2 = 5 m, where is the center of mass of these two objects?
3) Data for a project come from 30 randomly selected apple trees where each tree was assigned one time to be pruned: early-, mid-, or late- season and then the
why homogenization prolong milk shelf life
if I had enough money I would fly (begin with had)
If a quadrilateral is a parallelogram, then it’s opposite angles are ?